Technique 61: Self-ghettoization - Fischer, Nancy (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Teaching Objectives/Student Learning Outcomes:As a result of a request in an in-class exercise to draw a detailed map of the college/university’s city or town, students will recognize the degree to which they are unfamiliar with their surroundings. They will express their recognition of this unfamiliarity by their struggle or inability to produce a detailed rendition of the area’s streets, landmarks, neighborhoods and commercial areas.